PENGARUH KINERJA KEUANGAN, SIZE, PERTUMBUHAN PENJUALAN, DAN KEPEMILIKAN SAHAM TERHADAP STRUKTUR MODAL - Atiqoh, Zummatul; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
In the making of capital structure policy, a company requires to consider many factors in order to achieve the capital structure level which can minimize the average cost of capital and to maximize the firm value and companyâs assets. The purpose of this research is to test the influence of performace financial (profitability, liquidity and dividend policy), size, sales growth and stock ownership (managerial ownership and institutional ownership) to the capital structure. The sample collection technique has been done by using purposive sampling method, and based on the determined criteria, 44 manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2014 periods have been selected as samples. This research applies classic assumption test and multiple linear regressions analysis test which has been done by using statistic test of SPSS 20 version. The result of this research shows that institutional ownership have positive influence to the capital structure. Profitability, liquidity and dividend policy has negative influence to the capital structure. Meanwhile, size, sales growth and managerial ownership does not have any influence to the capital structure.Keywords: Performance Financial, Size, Sales Growth, Stock Ownership, Capital Structure